KEABSAHAN PUTUSAN PENGADILAN NEGERI SURABAYA NOMOR 117/PDT.SUS-PHI/2020/PN.SBY TENTANG PEMUTUSAN HUBUNGAN KERJA YANG DITINJAU DARI UNDANG-UNDANG CIPTA KERJA BESERTA PERATURAN PELAKSANANYA (STUDI KASUS : PT. WONOKOYO JAYA CORPORINDO) - Amadis Rasendhriya Yustiarachman; Soemali Soemali; Bambang Arwanto (Gapenas Publisher, 2023)
Humans as social beings generally have basic needs such as clothing, food and shelter. To fulfill these basic needs, humans are required to find a source of income, namely by working. In a job there is also a relationship called industrial relations. This study entitled